HUBUNGAN DERAJAT CEDERA KEPALA DENGAN OUTCOME PASCA TINDAKAN OPERASI PASIEN BEDAH SARAF DI RSUD WALED KABUPATEN CIREBON PADA TAHUN 2021-2022 - Ulfah, Siti Maria; Ayuwandari, Nenda; Sariadi, Dasa; Gunawan, Hendry; Max Emman, ⁠Irene; Wibisono, Rachmanda Haryo (Fakultas Kedokteran UGJ Cirebon, 2025)
Background: Head injury is a traumatic disturbance of brain function accompanied or without interstitial bleeding in the substance of the brain without interruption of brain continuity. The outcome of head injury is very important to know in order to prepare prevention measures, to prepare primary prevention strategies based on population size, and to prepare efficient and accurate treatment. Objective: To find out if there is a relationship between the degree of head injury and the postoperative results of neurosurgery patients at Waled Hospital in 2021-2022. Method: This type of research is qualitative research using an analytic observational method with a cross-sectional approach. The target population in this study were head injury patients who were treated at Waled Hospital, Cirebon Regency in 2021 – 2022. The sample size for this study was 50 people. Results: The degree of head injury in post-operative neurosurgery patients at Waled Hospital, Cirebon Regency in 2021-2022 has the most moderate head injuries (60%). The distribution of outcomes in postoperative neurosurgery patients at Waled Hospital, Cirebon Regency in 2021-2022 is mostly in the death category of 24 people (48%). The results of the Spearman correlation test showed that there is a p-value = 0.003, which means that there is a significant relationship between the degree of head injury and the postoperative outcome of neurosurgery patients at Waled Hospital, Cirebon Regency in 2021-2022. Then the results of the study found a value of r = 0.411, which means that there is a strong influence between the Degree of Head Injury and the Postoperative Results of Neurosurgery Patients at Waled Hospital, Cirebon Regency in 2021-2022. Conclusion: There is a significant relationship between the degree of head injury and the results of postoperative actions on Neurosurgery patients at Waled Hospital, Cirebon Regency in 2021-2022 Keywords: head injury, outcome, surgery in neurosurgery patients.